Efeitos agudos da técnica de empilhamento de ar na função pulmonar de indivíduos saudáveis - Pereira, Henrique Chiodi (Universidade Federal de São Carlos, 2025)
Air stacking (AS) is a lung expansion technique that uses positive pressure in the respiratory system, promoting an increase in lung volume. However, a complete pulmonary function assessment to evaluate the effects of this technique allows the identification of changes in important variables such as gas diffusion. Objectives: To assess the acute effects of the AS technique on pulmonary function in apparently healthy individuals, and to evaluate the association between the effects of air stacking on pulmonary function and heart rate variability. Methods: This was a randomized controlled clinical trial with apparently healthy individuals over 18 years of age, of both sexes. Participants underwent a one-day assessment and were then allocated into two possible groups: AS3x5 or control group. Both groups underwent pulmonary function testing through whole-body plethysmography, and heart rate variability (HRV) assessment using a heart rate monitor. On the same day, the intervention was carried out, consisting of the application of air stacking using an Ambu device attached to a mask and a positive expiratory pressure valve, in 3 sets of 5 repetitions. The difference between the groups was in the breath-holding phase of each set, as the control group was not instructed to sustain (hold) the air provided in each cycle. Results and Discussion: A total of 28 apparently healthy individuals participated in the study, with 15 in the Air Stacking (AS) group and 13 in the control group. The mean age was 21 years in both groups, with no significant differences in weight or height between them. Regarding pulmonary function variables, no significant differences were observed after the intervention in either group. Associations were found between RR intervals (Mean RR), which showed a positive correlation with FVC and FEV1. The RMSSD index also showed a positive correlation with FEV1, TLC, and the RV/TLC ratio, while SD1 was positively correlated with FVC, FEV1, TLC, and RV/TLC. Conclusion: The findings of this study indicate that air stacking (AS) in apparently healthy individuals did not produce acute increases in most pulmonary function variables, except for functional residual capacity after 20 minutes of technique application. Additionally, FVC and FEV1 were associated with greater data complexity and parasympathetic activity in HRV.
Acute effects of air stacking technique on pulmonary function in healthy individuals
Keywords: Função pulmonar; Expansão pulmonar; Empilhamento de ar; Pulmonary function; Lung expansion; Air stacking; Variabilidade da frequência cardíaca; Heart rate variability; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar